Comparison of learning effectiveness between physical classroom and online learning for dental education during the COVID-19 pandemic - Julia Yu-Fong Chang; Ling-Hsia Wang; Tzu-Chiang Lin; Feng-Chou Cheng; Chun-Pin Chiang (Elsevier, 2021)
Background/purpose: Online learning has been used to continue dental education activities during the coronavirus disease 2019 (COVID-19). This study aimed to compare the learning effectiveness between physical classroom and online class learning for dental education during the COVID-19 pandemic by the questionnaire survey. Materials and methods: A questionnaire-based online survey was used to evaluate the learning effectiveness on the dental students who took the compulsory course entitled "oral pathology and diagnosis" in School of Dentistry, National Taiwan University in 2021. Student's t-test and Mann-Whitney U test were used to analyze the difference in learning effectiveness between physical classroom and online class learning for dental education during the COVID-19 pandemic. Results: In this study, dental students tended to have a viewpoint that the learning effectiveness of online class learning was better than that of physical classroom learning. On the contrary, they tended to have a viewpoint that the convenience and fairness of physical classroom examination was better than that of online examination (all P-values < 0.001). Conclusion: We conclude that our dental students are ready to take online courses. In terms of blended learning courses, the combination of physical classroom and online courses is the future trend of dental education. At this moment, dental schools must prepare their abilities for the implementation of online courses to respond to the COVID-19 pandemic and the next crisis, as well as for the needs of future dental education.